VIAGEM E INVESTIGAÇÃO NA GRÉCIA ARCAICA - Koike, Katsuzo (PHOÎNIX, 2020)
The purpose of this article is to discuss the role of the voyages in the greek investigation about the world in the Archaic Period. Basically, the greek 'historie' had two aims: to explore other places and peoples and to research on the 'physis '. These voyages had a distinguished place in the greek culture for the practice of investigation which instigated the greek desire to the exploration of the world and its mysteries.